Genetic parameters of production traits in Murrah buffaloes - SETHI, R K; KHATKAR, M S (The Indian Journal of Animal Sciences, 2013)
First lactation records on 615 Murrah buffaloes from 1971 to 1994 were analysed. Least- square means for total milk yield,lactation length, 301-day yield, peak yield and wet average during first lactation were 1 693±29.7, 335±5.1, 1550:1:23.8, 7.9%0.10 and 5.10:1:0.07 respectively. Effect of periods was significant (P< 0.01) on all the traits while season of calving influenced lactation length only. Age at first calving significantly influenced total milk yield, 301-day yield and wet average. The heritabilities for the 5 traits were 0.16±0. 10,0.29%0. 11, 0.16%0.10, O. 17±0. to and 0.20±0. 11 respectively.